Does changing policy to disallow body checking reduce the risk of concussion in 11 and 12-year-old ice hockey players?. Issue 5 (11th March 2013) - Emery, C A; Macpherson, A; Kang, J; Hagel, B; Black, A; Romiti, M; Meeuwisse, W H
Abstract : Objective: The objective of this study was to determine if the risk of concussion differed for non-elite Pee Wee ice hockey players (ages 11–12) in leagues where Body Checking (BC) is permitted (Alberta, Canada) versus leagues where policy no longer permits BC (Ontario, Canada). Design: Cohort study. Setting: Community ice rinks and sport medicine clinics during the 2011/12 season. Participants: Forty-four teams from Alberta (n=658) and 32 from Ontario (n=258) participated. Players were from non-elite Pee Wee teams (lower 70% of divisions of play). Assessment of Risk Factors: Non-elite Pee Wee ice hockey leagues where BC is permitted (Alberta) compared to leagues where policy no longer permits BC (Ontario). Main Outcome Measurements: Players with a suspected concussion were identified by a team therapist or safety designate and referred to a sport medicine physician. Results: There were 83 concussions (Incidence Proportion (IP)=12.61 (95% CI; 10.17 to 15.4)) in Alberta and 11 concussions (IP=4.26 (95% CI; 2.15 to 7.5)) in Ontario. The Concussion Risk Ratio was 2.96 (95% CI; 1.6 to 5.46). Overall, 76% of players identified with a concussion were assessed by a physician. Conclusions: There was a 3-fold increased risk of concussion in non-elite Pee Wee ice hockey players in leagues where BC is permitted compared to a cohort where BC is no longer permitted. These findings have important implications for further BC policy change to reduce the public health burden of injury and concussion in youth ice hockey. Acknowledgements: The University of Calgary Sport Injury Prevention Research Centre is one of the International Research Centres for Prevention of Injury and Protection of Athlete Health supported by the International Olympic Committee. We also acknowledge the support of Max Bell Foundation, Alberta Innovates Health Solutions and the Alberta Children's Hospital Institute for Child and Maternal Health (Alberta Children's Hospital Foundation).